Common mystical themes of the spiritual Masnavi of Rumi and Golshan Raz by Sheikh Mahmoud Shabestari - Ghadmalsaltani, Saeedeh (2020)
There are many pure mystical themes and ideas in the thoughts of Rumi Jalaluddin Mohammad and Sheikh Mahmoud Shabestari. The main purpose of this research is to study the common themes in Rumi and Golshan Raz Shabestari's Masnavi and the sub-objectives are to study the dimensions of Shabestari's influence and follow-up on mystical issues and to study intellectual differences. Rumi and Shabestari and reviewing its arguments and comparing the quality of methods of expressing mystical issues in Masnavi and Golshan Raz. The present study is of a fundamental type. The research method of this research is descriptive-analytical and the results are library. The method of data collection was through recording and taking notes from reliable sources. The results of this research show that Rumi and Shabestari in many cases revealed the same mystical themes in Masnavi and Golshan. Common themes in Masnavi and Golshan Raz are the unity of existence and the multiplicity of existence, existence is of divine light, both worlds are the manifestation of the appearance of God; The veil of the human way, the imaginary of the universe, the loving look at God. The science of religion, distance from oneself, the effects of divine manifestation, the discredit of the world, etc.